The Analysis of Students' Speaking Ability in Speech At English Literature Department of Mahasaraswati Denpasar University - Satriawan, Ketut; Scolastika, I Made (Journal of Language and Applied Linguistics, 2025)
This study aimed to ascertain the abilities and difficulties in Speaking English of the third-semester students in the 3D class of the English Literature Department at Mahasaraswati Denpasar University. This research looked specifically at students' speaking skills. This research used descriptive quantitative methods. The approach of purposive sampling was adopted in this research. Eighteen students from the 3D class made up the sample for the research. The method the researcher used to determine speaking ability in speech was a speaking test. This research was conducted via WhatsApp. For instance, students are required to give a speech while it is being recorded on camera. Thus speaking ability will be examined in this research. Then, the researcher and inter-rater assessed their speaking. As a result, the findings of this study showed that three students had Excellent speaking ability, seven students had a good speaking ability, six students had Average speaking ability, and two students had Fair speaking ability. Pronunciation was the hardest part for the students, followed by fluency, comprehensibility, grammar, and vocabulary. In conclusion, the students generally have good speaking ability, and the pronunciation component is the greatest challenge for the students.